Design of Natterins-based peptides improves antimicrobial and antiviral activities - Gabrielle L. de Cena; Dayane B. Tada; Danilo B.M. Lucchi; Tiago A.A. Santos; Montserrat Heras; Maria Juliano; Carla Torres Braconi; Miguel A.R.B. Castanho; Mônica Lopes-Ferreira; Katia Conceição (Biotechnology Reports)
The biochemical analysis of animal venoms has been intensifying over the years, enabling the prediction of new molecules derived from toxins, harnessing the therapeutic potential of these molecules. From the venom of the fish Thalassophryne nattereri, using in silico methods for predicting antimicrobial and cell-penetrating peptides, two peptides from Natterins with promising characteristics were synthesized and subjected to in vitro and in vivo analysis. The peptides were subjected to stability tests and antimicrobial assays, cytotoxicity in murine fibroblast cells, antiviral assays against the Chikungunya virus, and the toxicity on G. mellonella was also evaluated. The findings underscore the peptides' robust stability under varying temperatures and pH conditions and resistance to proteolytic degradation. The peptides demonstrated significant antimicrobial efficacy, minimal cytotoxicity, and low hemolytic activity. Although their antiviral efficacy was limited, they showed potential at specific stages of viral replication. The in vivo toxicity tests indicated a favorable safety profile. These findings suggest that this approach can aid in the development of antimicrobial agents, offering a faster and personalized method to combat microbial infections, and represent a promising discovery in venom biotechnology research.